I mulini a vento della lettertura russa. La figura del Don Chisciotte nell'immaginario culturale slavo - Stefania Salvino (Im@go. A Journal of the Social Imaginary, 2022)
The windmills of Russian literature. The figure of Don Quixote in the Slavic cultural imagination. Literature in Russia has always performed a function of substantial importance, shaping up to be as one of the places in which the public sphere could most express itself. The materialization in the literary sphere of critical currents of thought and discursive practices by the intelligentsia has given rise to very animated debates that have profoundly affected Russian cultural life, even in the face of the presence of censorship more and more insidious, which amplified the passion with which the various issues were discussed. Among these, the relationship with Europe – and its 'cultural' products – has always embodied a central node in the identity definition of Russia itself. Cervantes' novel also fits into this framework, presenting itself as one of the European works from which it is not possible to leave out of consideration. Its appearance triggers a "russification process" which will lead to a deepening of themes and characters, operating parallels and reformulations of figures and myths typical of Russian literature.